Electronic crime and its legal dimensionComparison study betwen Algerian and Palestinian legislation (Numerus academy review, 2026)
Electronic crimes are considered a result of bad use for IT revolution , it's connects and depends on it , and this is why electronic crimes are given a special legal character whichrecognize it from other typical crimeswhether in its nature , content , range , ot types , even in the privacy and personality of those who commit electronic crimes, compared tothe normal type of crimes because it's fast to happen and developed according to the development of the technlogical means.On the base of internation legislations that issued laws to fight the electronic crimes , the Algerian and Palestinian legislator stood against those crimes through adjustments on the public and private laws which matters to such crimes, especially Punishments Law andAlgerian Code of Criminal Procedure, and the sentence of 2018, to fight electroniccrimes, in order to decrease it and issue punishments to reduce effects of this kind of new crimes which targets individuals, data, and states, and make a huge burden whith huge losses in different life sectors, and represent ' electronic colonialism ' in it's ugliestpicture..